Pengenalan Akan Allah Menurut Hosea 6:6 dan Relevansinya Dimasa Kini Bagi Orang Percaya - Welong, Gabriela Avril (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2023)
The purpose of this research is to emphasize the knowledge of God as articulated in Hosea 6:6. This verse serves as a key to understanding the relationship between God and His people, highlighting that knowing Him is far more valuable than religious rituals often performed without awareness or sincerity. According to Tjatur Raharso Yustinus et al. in "Pengenalan akan Allah," a deep understanding of God is fundamental for authentic faith, reflecting the loyalty of believers towards Him. Supriyadi in "Teologi Hosea" explains that the historical context of Hosea reveals Israel's entrapment in ritualism devoid of genuine connection with God, stressing that knowledge of God should transcend mere intellectual understanding and lead to a real spiritual experience. Widyastuti further asserts that a personal relationship with God enriches spiritual life and influences our interactions with others, urging that knowing God should inspire us to live in love and obedience, serving as witnesses of His love to others.